Integrated geoelectrical resistivity, hydrogeochemical and soil property analysis for groundwater investigation in north Kelantan, Malaysia / Nur Islami - Islami, Nur (2012)
Integrated geoelectrical resistivity, hydrogeochemical and soil property analysis methods were used to study the groundwater characteristics and their associated problem in North Kelantan, Malaysia. A total area of 487 km2 in this study is divided into three areas named Area 1, Area 2, and Area 3. The division is based on the geological and the environmental condition existing in the area. A pilot investigation was done prior to the main investigation in the Area 1. From the surface to depths of 75 cm, a lower average resistivity was obtained in former regularly-fertilized site (around 0.37 times less than in non-fertilized site). The presence of nitrate and chloride contents in pore water reduced the resistivity values despite the low moisture content. In the southern region of Area 1, concentration of nitrate is considered to be high (>20 mg/l). In particular, at one of the catchment zone within palm oil plantation, nitrate concentration is found 140 mg/l. The geoelectrical model shows lower resistivity values (around 18 ohm.m) at the sites with relatively high nitrate concentration in the groundwater (> 20 mg/l). Conversely, the sites with low nitrate concentration exhibit the resistivity values to be higher (>35 ohm.m). One of the fundamental results here is that the nitrate content in pore soil is good correlated to the resistivity measurements. The thickness of the aquifer ranges from 5 to 15 m and 25 to 40 m in the southern and northern of Area 1, respectively. Basement and groundwater potential maps are generated from the interpolation of an interpreted resistivity model. The geometry of potential aquifer is easily delineated from depth slice resistivity distribution and developed geological model. ii A novel investigation in evaluation and monitoring of chemical fertilizer using geoelectrical method has been examined in the site where the nitrate concentration tends to be higher (palm oil plantation and tobacco area). In the palm oil plantation which the soil condition is semi-pervious characters, the hydrogeochemical measurements indicate that the cations content are relatively similar for every time lapse measurement. However, relatively higher changes of anions content occur near surface to a depth of 1 meter. Of particular interest is the nitrate concentration above the limit for safe human consumption as it returns to the initial value about 100 days after fertilization. In tobacco area which soil condition is in border line of semi-pervious and pervious characters, a similar fertilizer monitoring show that the nitrate concentration higher than the nitrate concentration in the palm oil area. Although amount of urea introduced in the tobacco area is 0.6 less than in palm oil plantation, but the growth of nitrate bigger around 1.4 more than in palm oil plantation area. The pH values for the whole area range from 4.11 (minimum in Area 1) to 8.2 (maximum in Area 3), indicating that the groundwater is slightly acidic to slightly basic. The pH distribution is recognized that it has increasing trend from the south to the seaward. All the cation content is safe for human consumption except Fe. In the Area 1, the shallow groundwater sample (< 11 m depth) has a lower Fe concentration (0-0.3 mg/l). Whilst in the Area 2, a relatively higher (0.3 – 3 mg/l) Fe concentration is found in groundwater at the same depth interval in Area 1. In the deeper aquifer of Area 2 and Area 3, Fe concentration exceeds far above safe for human consumption (0.3 - 14 mg/l). A novel study on using geoelectrical resistivity method for heavy metal investigation in aquifer system is demonstrated here. Soil chemical analysis shows that in the zone of lower resistivity value (< 15 ohm.m), Fe and Al concentrations are relatively high (average of 40000 mg/kg and 68000 mg/kg, iii respectively). Lower resistivity value in the middle to the northwestern region of Area 2 is confirmed due to the high Fe and Al in the soil. This also is supported by the almost total lack of anion content in groundwater, while higher resistivity value in aquifers (> 40 ohm.m) is found in the zone with relatively lower Fe concentration in the groundwater (0-03 mg/l). Fe concentration in the soil has a positive linear correlation with Fe concentration in the groundwater, while Al concentration in groundwater has no correlation with Al concentration in soil. The possibility of high heavy metal in the aquifer is easily delineated in depth slice resistivity distribution. It extends from the north of Boundary Range Composite Batholith to the northwest. In some sites, shallow aquifer has direct contact with the surface which the surface water can infiltrate to the aquifer directly. This can be observed clearly in the geoelectrical model. In the site around Pengkalan Datu River, there is an indication of the shallow aquifer connected to the deeper aquifer. Improvement on geoelectrical resistivity interpretation and imaging of the groundwater potential in the coastal area has been performed. Percentage content of seawater in the pore soil, the source of the soil samples and the percentage of clay content in the soil samples influence significantly the resistivity reading. An increase in the percentage of seawater content decreases the resistivity value drastically. The salt/brackish water make a small slope in the shallow aquifer from the beach to the landward until reach at a depth of around 10 m below 2 km from the beach line. Small slope shape and decreasing percentage of seawater content in the shallow and deeper aquifer is clearly seen through the geoelectrical resistivity model. The resistivity value is decreased to the seaward and increased to the landward. The brackish-fresh water interface in the interval depth of around 20-35 m curve toward the direction of water flow in the area around Pengkalan Datu and Kelantan River. This indicates that there is a possibility of groundwater in the aquifer being influenced by the river water.